“You're Native but You're not Native Looking”: A Critical Narrative Study Exploring the Health Needs of Aboriginal Veterans Adopted and/or Fostered During the Sixties Scoop - Abdulwasi, Munira; Evans, Marilyn; Magalhaes, Lillian (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2016)
This study employed a critical narrative approach to examine the experience of Aboriginal Veterans in Canada adopted and/or fostered during the Sixties Scoop. The objectives of this study was to: 1) understand lived experiences of Aboriginal veterans adopted and/or fostered during the Sixties Scoop, 2) investigate health needs articulated by this population, and 3) provide suggestions for the creation of health services to aid Aboriginal veterans adopted and/or fostered during the Sixties Scoop with their health needs. Individual interviews were audio-recorded and conducted with eight participants from across Canada. All interviews were transcribed verbatim and analyzed using the holistic-content model (Lieblich, Tuval-Mashiach & Zilber, 1998). Data analysis of the interviews uncovered three overarching themes: a) sense of belonging, b) racism: experienced and perceived, and c) resilience: not giving up in the face of adversity. Two main health needs conveyed by the participants included mental health care and support to fight substance abuse. More awareness regarding the historical realities experienced by this population and the impact this may have on their overall health is needed. Increased coordination between Veterans Affairs Canada (VAC), Royal Canadian Legion (RCL), National Aboriginal Veterans Association (NAVA), Aboriginal Veteran Autochthones (AVA), and Aboriginal agencies is needed to address the mental health needs experienced by this group of veterans.